Does Compensation Important? The Effect of Compensation on Teachers Performance in Vocational High School - Windasari Windasari; Muchammad Zulham Yahya (Universitas Pendidikan Mandalika (UNDIKMA), 2021)
The purpose of this study was to determine the effect of compensation on the teacher performance in vocational school. This research used a quantitative approach. Data collection technique was by distributing a questionnaire using a five-likert scale. The sampling technique used was cluster random sampling. Samples taken from each school amounted to 3 teachers from each department, so there were 42 respondents from 5 schools. Validity test used the Pearson product moment. The analysis technique used to answer the research hypothesis uses simple linear regression. The results showed that teacher compensation had an effect on teacher performance in vocational high school.